2012
DOI: 10.1161/atvbaha.112.300627
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide–Releasing Aspirin Derivative ACS14 Exerts Strong Antithrombotic Effects In Vitro and In Vivo

Abstract: Objective-Hydrogen sulfide (H 2 S)-releasing NSAIDs exert potent anti-inflammatory effects beyond classical cyclooxygenase inhibition. Here, we compared the platelet inhibitory effects of the H 2 S-releasing aspirin derivative ACS14 with its mother compound aspirin to analyze additional effects on platelets. Methods and Results-In platelets of mice fed with ACS14 for 6 days (50 mg/kg per day), not only arachidonic acidinduced platelet aggregation but also ADP-dependent aggregation was decreased, an effect that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 46 publications
1
26
0
1
Order By: Relevance
“…19) It is noteworthy that ACS14, but not aspirin, causes phosphorylation of VASP in human platelets. 18) These reports are consistent with the present finding that NaHS also blocked ionomycin-induced aggregation in rabbit platelets, suggesting that NaHS interferes with not only the upstream but also downstream signals of cytosolic Ca 2+ mobilization probably through the cAMP/PKA pathway. Nonetheless, in our preliminary experiments, we could not find appropriate conditions in which elevation of cAMP levels in rabbit PRP following addition of NaHS was detectable (data not shown), whereas our ongoing study still focuses on effects of NaHS on cAMP levels in PRP and washed platelets from rabbits and other species.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…19) It is noteworthy that ACS14, but not aspirin, causes phosphorylation of VASP in human platelets. 18) These reports are consistent with the present finding that NaHS also blocked ionomycin-induced aggregation in rabbit platelets, suggesting that NaHS interferes with not only the upstream but also downstream signals of cytosolic Ca 2+ mobilization probably through the cAMP/PKA pathway. Nonetheless, in our preliminary experiments, we could not find appropriate conditions in which elevation of cAMP levels in rabbit PRP following addition of NaHS was detectable (data not shown), whereas our ongoing study still focuses on effects of NaHS on cAMP levels in PRP and washed platelets from rabbits and other species.…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, the therapeutic significance of H 2 S donors including ACS14 as anti-platelet or anti-thrombotic agents has been reported. 18) It is particularly of interest that combined application of NaHS and dipyridamole, a commercially available anti-platelet drug, exerted synergistic effects in the present study (see Fig. 4B).…”
Section: Discussionmentioning
confidence: 57%
“…The reaction of MG with arginine produces hydroimidazolones such as Nε-(5-hydro-5-methyl-4-imidazolon-2-yl)-ornithine and argpyrimidine [26], whereas with lysine it forms Nε-carboxyethyllysine CEL [27]. Thus, ACS14 has the potential to prevent the harmful effects of elevated MG and also provide antithrombosis [28] in diabetic patients, who have an increased risk of developing cardiovascular complications. We have previously shown that H 2 S provided by NaHS decreases MG levels in VSMCs [18].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that LIMK1 knockout selectively affected GPIb-IX-dependent TXA 2 production and signal amplification but had no negative effect on TXA 2 production and platelet responses induced by GPIb-IX-independent platelet agonists. This feature is distinct from the effects of cyclooxygenase inhibitors (such as aspirin [37][38][39] ) and TXA 2 receptor knockout, 40 which affect the TXA 2 pathway induced by all platelet agonists and thus are important in both thrombosis and hemostasis. Our study therefore not only reveals a new mechanism for GPIb-IX signaling and a novel function of LIMK1 but also a potential molecular target for the development of an antithrombotic with minimal bleeding side effect, although it is important to further investigate the role of LIMK1 under various hemostatic and thrombotic conditions.…”
Section: Discussionmentioning
confidence: 99%